Colonization as a Factor of Russian History in the Understanding of the Scholars of the 19th – early 20th Centuries - Nina S. Tsintsadze (Журнал Фронтирных Исследований)
The article contains an overview of research practices of the 19th – early 20th on Russian colonization understood as the settlement and economic development of empty or sparsely populated territories. The tasks included the study of the ideas concerning territory development, environment influence, understanding the role of colonization in the formation of the Russian state, as well as the significance of the colonization theory for historiography. The range of sources included scientific works by more than 20 scholars. Among the authors there are thinkers of different scientific schools and trends, which allowed us to consider a wide range of approaches to understanding the phenomenon of the colonization of Russia. Attention is paid to the analysis of both integral and regional interpretation of the colonization process. The theoretical and methodological basis for the study was the concept of “spatial turn”. It is shown that the colonization theory has proven productive in identifying the features of the historical evolution of Russia through the prism of its territorial growth and geographical conditions. Pre-revolutionary scholars noted that the expansion of the country was facilitated by the large capacity of the space of the north-eastern part of the European continent. The predominantly peaceful, but uneven and drawn-out character of colonization with a touch of permanence was emphasized. Researchers have identified its causes, directions, forms and consequences. Space was perceived as a valuable resource, and its scale as an achievement of the joint efforts of the state and society. The vastness of the state territory contributed to the establishment of a strong centralized power. It is concluded that the colonization theory has expanded and enriched historiography with historical, geographical and regional studies. It became one of the metanarratives of historical science in the modern period. Within its framework, the following problematic issues were raised and resolved: the factors of the formation of state territory, the peculiarities of its settlement, the spatial organization of the country. The colonization theory retains a high heuristic potential for the postmodernist study of the genesis of the space of the Russian state, including in the trend of the history of the frontier.